Stability Analysis of Nonlinear Systems with Slope Restricted Nonlinearities - Xian Liu; Jiajia Du; Qing Gao (The Scientific World Journal)
The problem of absolute stability of Lur’e systems with sector and slope restricted nonlinearities is revisited. Novel time-domain and frequency-domain criteria are established by using the Lyapunov method and the well-known Kalman-Yakubovich-Popov (KYP) lemma. The criteria strengthen some existing results. Simulations are given to illustrate the efficiency of the results.